A Website Content Analysis of Corporate Animal Welfare Messaging - Olivia Morris; Jefferson D. Miller; Isabel Whitehead (Journal of Applied Communications, 2019)
The purpose of this study was to identify and describe the nature of corporate positions on animal welfare available on the websites of five meat producing companies in the U.S. The results of the content analysis illustrated that there were common topics among the dialogs the companies were willing to open related to their animal welfare positions. The companies typically took a general approach to animal welfare topics, commonly focusing on their corporate policy and their commitment to animal welfare. While each company focused on a unique combination of topics, companies commonly avoided mentioning more specific and possibly controversial topics and instead chose to focus on big-picture topics such as a commitment to sound animal welfarepractices. Each company used a particular set of frames to couch individual animal welfare messages for consumers. The most common frame led was that the company is an industry leader in animal welfare. Eighteen thematic terms related to livestock production and handling emerged through the content analysis. Of those, animal handling and humane were clearly the most commonly used terms. Future research should include matching these content analysis results with the existing communication strategies of each company, conducting more content analyses on animal protein companies’ other media outlets, as well as further exploring the presence of frames, topics, and terminology in news coverage in comparison to the online messages of animal protein companies.
Keywords: Content analysis; animal welfare; protein industry